Perceptions of Barriers to Effective Obesity Care: Results from the National ACTION Study. Issue 1 (31st October 2017) - Kaplan, Lee M.; Golden, Angela; Jinnett, Kimberly; Kolotkin, Ronette L.; Kyle, Theodore K.; Look, Michelle; Nadglowski, Joseph; O'Neil, Patrick M.; Parry, Thomas; Tomaszewski, Kenneth J.; Stevenin, Boris; Lilleøre, Søren Kruse; et al.
Abstract : Objective: ACTION (Awareness, Care, and Treatment in Obesity maNagement) examined obesity‐related perceptions, attitudes, and behaviors among people with obesity (PwO), health care providers (HCPs), and employer representatives (ERs). Methods: A total of 3, 008 adult PwO (BMI ≥ 30 by self‐reported height and weight), 606 HCPs, and 153 ERs completed surveys in a cross‐sectional design. Results: Despite several weight loss (WL) attempts, only 23% of PwO reported 10% WL during the previous 3 years. Many PwO (65%) recognized obesity as a disease, but only 54% worried their weight may affect future health. Most PwO (82%) felt "completely" responsible for WL; 72% of HCPs felt responsible for contributing to WL efforts; few ERs (18%) felt even partially responsible. Only 50% of PwO saw themselves as "obese, " and 55% reported receiving a formal diagnosis of obesity. Despite HCPs' reported comfort with weight‐related conversations, time constraints deprioritized these efforts. Only 24% of PwO had a scheduled follow‐up to initial weight‐related conversations. Few PwO (17%) perceived employer‐sponsored wellness offerings as helpful in supporting WL. Conclusions: Although generally perceived as a disease, obesity is not commonly treated as such. Divergence in perceptions and attitudes potentially hinders better management. This study highlights inconsistent understanding of the impact of obesity and need for both self‐directed and medical management.